Some Thoughts on Christianity and Sports - Aragón Vargas, Luis Fernando (1991)
There is a need to discuss, starting from some basic Christian truths, to what extent the Christian and athletic ideals are compatible; how sports could help modern men and women to be better Christians, and what kind of difficulties will normally be encountered by the Christian athlete. This essay proposes a few biblical principles and discusses them as they relate to an athlete's experience.